Ionic columnar clustomesogens: associations between anionic hexanuclear rhenium clusters and liquid crystalline triphenylene tethered imidazoliums. Issue 32 (18th July 2018) - Camerel, F.; Kinloch, F.; Jeannin, O.; Robin, M.; Nayak, S. K.; Jacques, E.; Brylev, K. A.; Naumov, N. G.; Molard, Y.
Abstract : [Re6 Se8 (CN)6 ] 4− clusters combined with imidazolium-anchored triphenylene generate phosphorescent columnar mesophases with good film-forming properties. Abstract : Providing several functionalities to a single material is an emerging challenge with many industrial prospects in materials sciences. Self-assembled organic–inorganic hybrid materials endowed with emission properties are part of these new materials. While the inorganic moieties provide emissivity, the organic part confers nanostructuration and processability. Here we describe how columnar arrangements can be obtained by assembling, via electrostatic interactions, isometric anionic inorganic nanoemitters, namely [Re6 Se8 (CN)6 ] 4−, with imidazolium counter cations bearing triphenylene units. The resulting hybrids combine the emission of both components and energy transfer has been evidenced between both entities. Hole charge mobilities of the hybrid organic–inorganic columnar mesophases were also evaluated by the space charge limited current (SCLC) method.